If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2j = 4 Solving 6 + -2j = 4 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -2j = 4 + -6 Combine like terms: 6 + -6 = 0 0 + -2j = 4 + -6 -2j = 4 + -6 Combine like terms: 4 + -6 = -2 -2j = -2 Divide each side by '-2'. j = 1 Simplifying j = 1
| -(7/8)r=6 | | 16x-5=11x-25 | | 30-3x=5x-18 | | 1.75t-4.5=7.74 | | 1.6=7.6-5(k+11) | | y=-2y | | x=28+(-47) | | 3z-6=-6z-15 | | 6x^3-21x^2-12x=0 | | -3(8p+6)-2(6-17p)=3(2+3p) | | 3x^2+7x+30=0 | | -0.9x+8.19=-0.7x+4.79 | | (3/11)z=-5 | | lnx-2ln=ln^4 | | 4(m-3)=8m-40 | | 10=x+5-2x | | y-10=37 | | 14y^2=18 | | 7y+9+3y+9=143 | | a+17=-19 | | -4.5a=-32.4 | | -(5/9)k=2 | | x+56=x-23 | | 7x+9=4x+12 | | a+19=-17 | | (10t-5t+14)+(11t-8)= | | 5y+14-8y=-20 | | 7w-4w-3=12 | | 0.7x-0.3x+5=7 | | 3x=450 | | 84=20x | | 3x+4x-8=2(2x+5) |